The Effectiveness and Safety of Tripterygium wilfordii Hook. F Extracts in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Zhou, Ying-Yan; Xia, Xuan; Peng, Wen-Ke; Wang, Qin-He; Peng, Jian-Hong; Li, Yan-lin; Wu, Jian-Xiong; Zhang, Jian-Yong; Zhao, Yue; Chen, Xiu-Min; Huang, Run-Yue; Jakobsson, Per-Johan; et al. (Frontiers in Pharmacology, 2018)
Objective: To conduct a meta-analysis of the effectiveness and safety of Tripterygium wilfordii Hook. F (TwHF) extracts for the treatment of rheumatoid arthritis. Methods: A systematic literature search was conducted in PubMed, EMBASE, Cochrane, Medline, CNKI, SinoMed and WanFang Library till 12 July 2017. All included studies were analyzed with the use of the Review Manager 5.2 software according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement protocol. Results: Fourteen randomized controlled trials (RCTs) were identified. TwHF extracts provided a statistically significant improvement in grip strength (GS), swelling joint count (SJC) and morning stiffness (MS) compared with placebo (P<0.001). The meta analysis showed significant differences between TwHF extract-treated group and the DMARDs group in GS, MS, C-reactive protein (CRP) and tender joint count (TJC) (P<0.05), aside from ESR and SJC (P>0.05). The pooled results also displayed significant differences between the combination of TwHF extracts with DMARDs and the DMARDs alone group in ESR, CRP, SJC and TJC (P≤0.05). For the safety analysis, two trials favored TwHF extract-treatment and one trial favored non-TWHF extract-treatment in AEs (P<0.05). Eleven trials showed no statistically significant differences between TwHF extract-treated group and the DMARDs group (P > 0.05). Conclusions: The findings of this systematic review with meta-analysis indicate that TwHF extracts provides statistically significant and clinically important improvement in rheumatoid arthritis symptoms and has an acceptable safety profile.